Current status of Bioenergy in Portugal Portugal National Day Conference, EUBCE 2019 - Dias, J.; Gírio, F.; Mendes, I.; Beirão, D. (2019)
Biomass in Portugal represents about 13% of the total primary energy consumption, which accounts to about 50% of total RES share. Portugal´s Southern European geographical location, in the cross of the Atlantic and Mediterranean climate zones, enables a diversified agricultural and forest production leading to a diverse biomass feedstock for bioenergy and bioproducts production. Currently, a major issue in the country is the prevention of forest fires through a sustainable forest management taking into consideration economic, environmental, and social dimensions. Before 2020, it is planned the promotion of decentralized small-scale heat-producing biomass plants dimensioned for the locally identified heat needs (industrial heat networks, services or municipal equipment). The installation of advanced biorefineries is also being considered to fully deploy a fully sustainable bioenergy-based system towards the circular bioeconomy goal. The National Plan for Promotion Biorefineries (RCM nº 163/2017) is the national guideline for promoting next-generation biomass-based industries for 2030. This event will gather experts from industry and research into three sessions dedicated to heat and power applications, forest biorefineries, emerging technologies and biomass markets. The agenda includes presentations on: Role of biomass in the Portuguese energy system Thermal energy solutions for domestic uses Forest fuels for production of thermal energy for industrial applications Power production from residues using a rotary kiln Emerging technologies for biorefineries Biomethane for use in vehicles Kraft pulp and paper mills biorefineries Biorefining forest biomass towards a sustainable thinking about forest, natural resources and bioenergy A key-note speaker from Lithuania will present the BALTPOOL experience – Biomass traded as commodity, that will be followed by a roundtable to discuss the challenges and solutions for creation biomass markets linked to forest and land management.